1997
DOI: 10.1139/m97-035
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial endophytes in cotton: location and interaction with other plant-associated bacteria

Abstract: Investigations were conducted to determine if biological control agent Pseudomonas fluorescens 89B-61 could colonize cotton tissues systemically and if internal colonization by a known endophytic bacterium, Enterobacter asburiae JM22, was influenced by the presence of other plant-associated bacteria. Following seed treatment, Pseudomonas fluorescens 89B-61 colonized cotton roots both externally and internally at mean population densities of 8.7 × 105 CFU/g and 1.1 × 103 CFU/g, respectively. However, bacteria w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
18

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(55 citation statements)
references
References 8 publications
2
35
0
18
Order By: Relevance
“…In general, endophytic bacteria colonize the intercellular spaces and vascular systems of host plants, with only a few reports of intracellular colonization (9). Since endophytic bacteria are considered to compete with each other and with other endophytic organisms (such as fungi) for the limited space within the host plant (5,33), the endophytic bacteria that reside in seeds may have the advantage of being able to infect rapidly the next generation of plants.…”
Section: Resultsmentioning
confidence: 99%
“…In general, endophytic bacteria colonize the intercellular spaces and vascular systems of host plants, with only a few reports of intracellular colonization (9). Since endophytic bacteria are considered to compete with each other and with other endophytic organisms (such as fungi) for the limited space within the host plant (5,33), the endophytic bacteria that reside in seeds may have the advantage of being able to infect rapidly the next generation of plants.…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been shown that endophytic communities vary spatially in the plant (9) or may be dependent on the interaction with other endophytic or pathogenic bacteria (29).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, at a tissue level, the role of the cortex in root exudation versus that of the epidermis remains unknown. Although apoplastic loss may represent a slow diffusion pathway in comparison to direct loss from the epidermis (Canny 1995;Fleischer and Ehwald 1995), evidence suggests that gaps between epidermal cells (where apoplastic loss ultimately manifests itself) are strong regions of microbial colonization and therefore C availability (Quadt-Hallmann et al 1997;Watt et al 2006). Therefore more work is required to characterise apoplastic loss pathways from the root cortex and its contribution to maintaining the endo-and ectorhizosphere microbial community.…”
Section: Exudatesmentioning
confidence: 99%